Kepemimpinan Kepala Sekolah dalam Peningkatan Mutu Pendidikan di SMA A. Wahid Hasyim Tebuireng Diwek Jombang - Risyunida Utami; Asriana kibtiyah (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2022)
A leader is very influential in the course of the educational process. The leadership of the head of SMA A. Wahid Hasyim Tebuireng can be categorized as a democratic leader. This can be seen, one of which is from the way he makes decisions, he always includes his subordinates or staff in every decision-making process. Involvement of subordinates or staff in decision-making, it is expected that they feel they have a sense of responsibility in carrying out decisions. The quality of education is in accordance with national education standards. The supporting factor in improving the quality of education is the fulfillment of qualified human resources (HR). While the inhibiting factor is the lack of funds for quality improvement.